Illegal Tour Guides And Their Legal Implications For Tourist Protection In Bali - I Komang JUMENA; Jumena , I Wayan; Styawati, Ni Komang Arini (Protection: Journal Of Land And Environmental Law, 2026)
This article examines the legal implications of illegal tour guides on tourist protection and the sustainability of the tourism industry in Bali. The main objective of this study is to analyze the legal regulation governing tour guide services and to assess the impact of illegal tour guide practices on service quality, legal certainty, and tourist protection. This research employs a statutory approach, a conceptual approach, and a sociological approach. Primary data were obtained through interviews with licensed tour guides, tourism stakeholders, and relevant authorities, while secondary data were derived from legislation, legal doctrines, and academic literature related to tourism law. The analysis reveals that the presence of illegal tour guides contributes to declining service quality, unfair competition, weakened legal protection for licensed tour guides, and increased legal risks for tourists, particularly in situations involving accidents or insurance claims. The findings also indicate that existing regulations have not been optimally enforced, resulting in gaps between legal norms and actual practices in the tourism sector. This study concludes that strengthening supervision, law enforcement, and inter-institutional coordination is essential to ensure legal certainty, protect tourists, and maintain the quality and reputation of Bali as an international tourism destination